Oral Treatment With an Engineered Uricase, ALLN-346, Reduces Hyperuricemia, and Uricosuria in Urate Oxidase-Deficient Mice - Pierzynowska, Kateryna; Deshpande, Aditi; Mosiichuk, Nadiia; Terkeltaub, Robert; Szczurek, Paulina; Salido, Eduardo; Pierzynowski, Stefan; Grujic, Danica (Frontiers in Medicine, 2020)
Limitations in efficacy and/or tolerance of currently available urate-lowering therapies (ULTs) such as oral xanthine oxidase inhibitors, uricosurics, and intravenous uricase agents contribute to the development of refractory gout. Renal excretion is the major route of uric acid elimination, but the intestinal tract plays an increasingly recognized role in urate homeostasis, particularly in chronic kidney disease (CKD) where urate the renal elimination of urate is impaired. We targeted intestinal degradation of urate in vivo, with ALLN-346, an orally administered, engineered urate oxidase, optimized for proteolytic stability and activity in the gut. We tested ALLN-346 in uricase/urate oxidase deficient mice (URKO mice) with severe hyperuricemia, hyperuricosuria and uric acid crystalline obstructive nephropathy. A total of 55 male and female URKO mice were used in the two consecutive studies. These seminal, proof of concept studies aimed to explore both short-term (7-day) and long-term (19-day) effects of ALLN-346 on the reduction of plasma and urine urate. In both the 7 and 19-day studies, ALLN-346 oral therapy resulted in the normalization of urine uric acid excretion and significant reduction of hyperuricemia by 44% and 28% when therapy was given with food over 24h or was limited for up to 6 hours, respectively. Fractional excretion of uric acid (FEUA) was normalized with ALLN-346 therapy. Oral enzyme therapy with engineered urate oxidase (ALLN-346) designed to degrade urate in the intestinal tract, has the potential to reduce hyperuricemia and the renal burden of filtered urate in patients with hyperuricemia and gout, with and without CKD.